Administration of BNT162b2 mRNA COVID-19 vaccine to subjects with various allergic backgrounds - Ribak, Yaarit; Rubin, Limor; Talmon, Aviv; Dranitzki, Zvi; Shamriz, Oded; Hershkowitz, Isca; Tal, Yuval; Hershko, Alon Y. (Frontiers in Immunology, 2023)
The mRNA-based COVID-19 vaccine was introduced to the general public in December 2020. Shortly thereafter, safety concerns were raised due to the reporting of allergic reactions. Allergy-related disorders were suspected to be significant risk factors and the excipient polyethylene glycol was suggested to be a robust allergen.Methods: This is a retrospective study analysis. Subjects with putative risk factors for severe allergic reactions to the Pfizer-BioNTech BNT162b2 vaccine were referred for vaccination under observation at the Unit of Allergy and Clinical Immunology. Data was collected for each subject, including demographic details, medical history and previous reactions to any allergen. When appropriate, skin tests were done prior to vaccination.Results: A total of 346 subjects received 623 vaccine doses under observation. The study included patients with various allergy-related disorders (n=290) and those with allergy to a previous COVID-19 vaccine dose (n=56). Both groups showed female predominance (78% and 88%, p=NS). Patients without reactions to previous doses reported more drug allergy (80% vs. 39%, p<0.001) and previous anaphylaxis (64% vs. 14%, p<0.001). There was no difference in sensitivity to other allergens, including polyethylene glycol. Under observation, mild allergic reactions were noted in 13 individuals characterized by female gender (100%), a history of anaphylaxis (69%) and drug allergy (62%). In 7 subjects, allergy was treated with antihistamines while others recovered spontaneously.Our study demonstrates that vaccination under specialist-supervision is a powerful tool for reducing over-diagnosis of systemic reactions and for rapid and reliable collection of vaccine safety data.